Daya Dukung Pondasi Telapak Berselimut Pada Tanah Berlapis - Utomo, Niat Surgo; , Anto Budi Listyawan, S.T., M.Sc; , Ir. Renaningsih, M.T (2017)
Bearing capacity is the most important factor in planning a foundation. There needs to be an effort to increase the value of the bearing capacity. The blankets were installed at the bottom surface foundation can be useful as one of these solutions. Blankets are used to increase the bearing capacity of shallow foundation layered soil. This study penyuguhkan nine laboratory testing foundation circular shapes made of steel with a length diameter and length blankets different, the layered soil media to maintain the predictability of water content and method of compacting. Of the overall laboratory testing, it is known that the blanket is very effective to increase the carrying capacity values. With the blanket, the value of the carrying capacity could reach more besae of value if the carrying capacity without blankets. Blankets also can reduce the decline. In general decline in the wane, when reviewed at the same load value, ie 1 kN. Footing with the longest quilt show a decrease in best condition. And also when compared with medium sand, sand media have tilapia bearing capacity better than the layered soil media.